PENINGKATAN EFEKTIVITAS MANAJEMEN PENGELOLAAN PESANTREN DI PESANTREN ALWASILAH LILHASANAH ISLAMIC BOARDING SCHOOL - Rachma Zahra Nuraqila; Wiwi Alawiyah, Adi Rosadi (CV. ADIBA AISHA AMIRA, 2026)
This research aims to assess and understand the management practices at Pondok Pesantren Alwasilah Lilhasanah Islamic Boarding School, located in Sukabumi, West Java. The main focus is on how the school’s management creates an effective and efficient educational environment. The study uses qualitative methods with a case study approach, collecting data through observation, structured interviews, and document analysis. Findings indicate that while management at Pondok Pesantren Alwasilah Lilhasanah is systematic, improvements are needed in areas like facility management and staff development programs. The study highlights a conducive environment within the school based on observations and discusses both satisfaction and challenges among management and students. Overall, while management functions adequately, enhancing specific areas is crucial to optimize educational goals. Recommendations include improving facility management and enhancing staff development programs to achieve better educational outcomes.